Amniotomy Affects the Urine Protein Creatinine Ratio Accuracy in the Diagnosis of Preeclampsia [9C]. (May 2017) - Quinn, Sara; Lennon, Jessica; Gonzalez, Aaron Herrera; Dierking, Elizabeth; Anasti, James
Abstract : INTRODUCTION: Preeclampsia is a leading cause of obstetric related morbidity and mortality, making prompt diagnosis crucial. While the gold standard for evaluation of maternal urinary protein is a 24 hour urine collection, the spot urine protein creatinine ratio (Up/Ucr ratio) greater than 0.3 g/gcr has been instituted as an alternative. No studies have evaluated the effect of amniotomy, spontaneous or artificial, on the accuracy of the Up/Ucr ratio. We hypothesize the proteins and creatinine found in amniotic fluid may erroneously alter the test result leading to an incorrect diagnosis of preeclampsia. METHODS: We performed a case-control trial where each patient served as their own control. An initial random catch urine was obtained for Up/Ucr ratio in women with intact membranes. Following amniotomy a second random catch Up/Ucr ratio was obtained. The urine samples were analyzed in the hospital chemistry department and results compared for consistency. RESULTS: The 49 study patients had the following characteristics; Age: 28.8 ± 5.8y, Gravid: 2.7 ± 1.5, Gestational age: 39.1 ± 1.8wks, and BMI: 31.2 ± 6.6 kg/m 2 . Co-morbidities included 3 gestational diabetic, 2 chronic hypertensive and one preeclamptic patient. Post-amniotomy Up/Ucr ratio was significantly higher than Pre-aminotomy (1.1±2.1 vs 0.23 ± 0.15, p=0.001). The prevalence of Up/Ucr greater than 0.3 g/gcr was higher post amniotomy than pre-amniotomy (28 vs 8, p =0.001). CONCLUSION: Amniotomy results in false elevation of the Up/Ucr ratio. Obtaining urine via straight catheterization may be necessary to reduce false positive results.